Peningkatan Hasil Belajar Bahasa Inggris Siswa di Sekolah Alam melalui Pengembangan Model dan Media Pembelajaran Inovatif - Darmawan, I Nyoman Pasek; Kaldina, Vindi; Suntara, Reza Adriantika (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
English language skills of students are an important part of the quality of student learning in schools. This is considered important to support student competence as competent human resources in facing global progress. However, the low average English language score index still occurs in several schools, including Sekolah Alam Pangkal Pinang. Based on this, a Workshop on Developing Innovative Learning Models for Teachers and Implementing Innovative Learning Media was held by implementing more creative, innovative, and progressive learning models and methods at Sekolah Alam Pangkal Pinang. This activity was carried out using the service learning method through four stages of implementation, starting from investigation, preparation, action, and reflection. The results of this service implementation were the implementation of innovative learning models and methods by English teachers at Sekolah Alam Pangkal Pinang with improved learning outcomes based on the evaluation results carried out by the service team.